FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PEMAHAMAN AKUNTANSI (Studi Empiris pada Mahasiswa Akuntansi IBI Darmajaya Lampung) - Sri Maryati (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2017)
Motivation to learn a whole is said to be the driving force in the self-learning activities ofstudents cause, which ensures the continuity of learning. The principles of motivation in the learningprocess include: attention, relevance, confidence, and contentment. Learning style is a combination ofhow people absorb, organize and process information. Characteristics of learning modalities such asvisual, auditory, and kinesthetic. Behavioral dimension of learning is learning by individuals repeatedlyso it becomes automatic or spontaneous. Learning behavior characterized by accounting textbookreading habits, habits to learn, habit of visiting the library, and the preparation for exams.The level of understanding of accounting refers to the accounting value of the courses thatstudents have taken Auditing II and Accounting Theory. This study aimed to determine the effect oflearning motivation, learning behavior, and learning styles of the level of understanding of accountingempirical studies at the IBI Darmajaya Lampung majoring of accounting.